The effectiveness of using contemporary techniques in teaching geography from the point of view of public elementary school teachers in Marka Directorate of Jordan - Alnanah, Jum'ah Mohammad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the effectiveness of using contemporary techniques in teaching geography course in government basic schools in Marka Directorate of Jordan: 1- That (46 out of 65, and the rate of 70.76%) confirmed the effectiveness of the use of information and communication technology in teaching geography, and that (44 out of 65, and the rate of 67.7%) confirmed the effectiveness of the use of geographical maps in the teaching of geography, and that (43 out of 65, and the rate of 66.15%) They emphasized the effectiveness of the use of geographical information systems in the teaching of geography. 2- That (19 out of 65, and a percentage of 29.24%) confirmed the ineffectiveness of using information and communication technology in teaching geography, and that (21 out of 65, and a percentage of 32.3%) confirmed the ineffectiveness of using geographical maps in teaching geography, and that (22 out of 65, and a percentage of 33.85%) confirmed the ineffectiveness of using geographical information systems in teaching geography. In light of the results, a number of recommendations and suggestions were presented, including: developing the skills of geography teachers to use information and communication, geographic maps, and geographical information systems in teaching.